2009
DOI: 10.1002/j.0022-0337.2009.73.2.tb04652.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Critical Thinking Measurement of Dental Student Performance

Abstract: The educational application of critical thinking has increased in the last twenty years with programs like problem-based learning. Performance measurement related to the dental student's capacity for critical thinking remains elusive, however. This article offers a model now in use to measure critical thinking applied to patient assessment and treatment planning across the four years of the dental school curriculum and across clinical disciplines. Two elements of the model are described: 1) a critical thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 10 publications
0
44
0
2
Order By: Relevance
“…Johnsen et al suggested that there is a need to longitudinally assess critical thinking skills across the dental curriculum in order to best measure long‐term learning gains 5 . In our study, for both cohorts, the students who had the lowest scores on the initial assessment of critical thinking skills showed statistically significant improvements over time.…”
Section: Discussionmentioning
confidence: 47%
“…Johnsen et al suggested that there is a need to longitudinally assess critical thinking skills across the dental curriculum in order to best measure long‐term learning gains 5 . In our study, for both cohorts, the students who had the lowest scores on the initial assessment of critical thinking skills showed statistically significant improvements over time.…”
Section: Discussionmentioning
confidence: 47%
“…While critical thinking skills have been defined, no unifying skill set has yet been developed. Examples of critical thinking skill sets have been reported for treatment planning, search and critique of literature, evidence‐based dentistry, reflections, caries risk assessment, behavior management, geriatric risk assessment, and technology decision making 26 30 …”
Section: Dental Education Outcomes Needed To Address Changesmentioning
confidence: 99%
“…Critical thinking skillsets have been developed and reported for treatment planning, literature search, and critique, caries risk assessment, technology decision-making, EBD, geriatric risk assessment, IPP, reflections/situation analysis, behavior management, case presentation. [1][2][3][4][5][6][7][8][9] These peer-reviewed skillsets can aid in showing milestones so far established for explicit learning outcomes in critical thinking and can give insights to extend the boundaries to include conceptualizing the patient interaction. Emulation models in progress will demonstrate critical thinking skillsets deriving probing questions from the expert in social work and ethics.…”
Section: Introduction and Background On Models For Critical Thinking mentioning
confidence: 99%